DVD FORMAT AND PROCESS OF MAKING VIDEO EDITING USING SONY VEGAS PRO 8.0 - Yulina Yulina (JAKSTIK Journal, 2006)
In today's modern era, the need for entertainment is very important, especially in the business world. Therefore, the application of technology, the digital system is one correct solution in the process of filmmaking. In this case, may be helpful to learn the process of digital video editing using Sony Vegas Pro 8.0 software outputs Sony Creative Software.Â Â  The need for entertainment is very important, especially in the business world such as advertising and movie theater.